नेपालको सन्दर्भमा प्रयुक्त बहुभाषिक कक्षा शिक्षण सम्भाव्यताको अध्ययन {Feasibility Study of Multilingual Class Teaching in Nepalese Context} - शेर्पा Sherpa, दावा Dawa (Bikasko Nimti Shiksha (विकासको निम्ति शिक्षा), 2024)
प्रस्तुत लेख उद्देश्यमूलक गुणात्मक अध्ययन ढाँचामा तयार गरिएको छ । भाषा प्रयोक्ताका दृष्टिले नेपाल बहुभाषिक राष्ट्र हो । नेपालमा बोलिने १२४ वटा मातृभाषामध्ये एक लाखभन्दा बढी वक्ताहरूले बोल्ने एक्काइसवटा भाषाहरूमा कोशी प्रदेशका १०९ मातृभाषीमा क्रमश: नेपाली, मैथिली र लिम्बू, मदेस प्रदेशका ६२ मातृभाषीमा मैथिली, भोजपुरी र बज्जिका, वागमती प्रदेशका १०९ मातृभाषीमा नेपाली, तामाङ र नेपाल भाषा, गण्डकी प्रदेशका ७४ मातृभाषीमा क्रमश: नेपाली, मगर र गुरुङ, लुम्बिनी प्रदेशका ६८ मातृभाषीमा नेपाली, अवधि र थारू, कर्णाली प्रदेशका ४९ मातृभाषीमा नेपाली, खस र मगर र सुदूरपश्चिम प्रदेशका ७४ मातृभाषीमा नेपाली, डोटेली र थारू मातृभाषी वक्ताहरू पाइएका छन् । कोशी प्रदेशका १०५ दोस्रो भाषीमा नेपाली, मैथिली र बान्तवा, मदेस प्रदेशका ६८ दोस्रो भाषीमा नेपाली, मैथिली र भोजपुरी, बागमती प्रदेशका १०० दोस्रो भाषीमा नेपाली, तामाङ र नेपाल भाषा, गण्डकी प्रदेशका ७२ दोस्रो भाषीमा क्रमश: नेपाली, तामाङ र मगर, लुम्बिनी प्रदेशका ६४ दोस्रो भाषीमा नेपाली, अवधि र थारू कर्णाली प्रदेशका ३८ दोस्रो भाषीमा नेपाली, मगर र उर्दू र सुदूरपश्चिम प्रदेशका ५० दोस्रो भाषीमा नेपाली, डोटेली र थारू दोस्रो भाषी वक्ताहरू पाइएका छन् । बहुभाषिक कक्षाका शिक्षणका लागि मैथिली, भोजपुरी, अवधी, लिम्बू, मगर र नेवारी मातृभाषीका कक्षा १ देखि १२ सम्मका पाठ्यक्रम तयार भएका छन् । यी मातृभाषी र दोस्रो भाषी वक्ताहरूले प्रदेशगत रूपमा आफ्नो मातृभाषा र दोस्रो भाषा नेपाली तथा उच्च शिक्षा अध्ययनको माध्यम अङ्ग्रेजी भाषासमेतको गर्दा नेपालको भाषानीति बहुभाषिक हुनु आवश्यक छ ।{The present article has been prepared in a purposive qualitative study design. Nepal is a multilingual country in terms of language users. Of the 124 mother tongues spoken in Nepal, twenty-one languages are spoken by more than one lakh speakers. Among the 109 mother tongues spoken in Kosi Province, Nepali, Maithili and Limbu are the languages spoken by more than one lakh speakers; among the 62 mother tongues spoken in Madhes Province, the languages spoken by more than one lakh speakers are Maithili, Bhojpuri and Bajjika. Similarly, among 109 languages spoken in Bagmati Province Nepali, Tamang, and Nepal Bhasa; among 74 mother tongues spoken in Gandaki Province, Nepali, Magar, and Gurung; among 68 mother tongues spoken in Lumbini Province, Nepali, and Tharu; out of 49 mother tongues spoken in Karnali Province, Nepali; Khas and Magar; and out of 74 mother tongues spoken in Sudurpashchim Province, Nepali, Doteli and Tharu are the languages spoken by more than one lakh speakers. Similarly, Nepali, Maithili, and Bantwa are found to be spoken as second languages in Koshi Province; Nepali, Maithili, and Bhojpuri in Madhesh Province; Nepali, Tamang, and Nepal Bhasha in Bagmati Province; Nepali, Tamang, and Magar in Gandaki Province; Nepali, Awadhi, and Tharu in Lumbini Province; Nepali, Magar, and Urdu in Karnali Province; and Nepali, Doteli, and Tharu are found to be spoken as second languages in Sudurpashchim Province. Maithili, Bhojpuri, Awadhi, Limbu, Magar, and Newari mother tongues have been prepared for classes 1 to 12 for teaching in multilingual classes. Since the mother tongue of these native and second language speakers is Nepali and the second language as well as the medium of higher education is English, there is a need to make Nepal's language policy multilingual.}